Cardiac Conduction System Anomalies and Sudden Cardiac Death: Insights from Murine Models - Aranega, Amelia E.; de la Rosa, Angel J.; Franco, Diego (Frontiers in Physiology, 2012)
The cardiac conduction system (CCS) is composed of a group of myocardial tissues that control and coordinate the heart. Alterations in the CCS – especially in the His–Purkinje system, have been identified as a major cause of lethal arrhythmias. Unstable arrhythmias secondary to channelopathies significantly increase the risk of sudden cardiac death (SCD). SCD is a major contributor to mortality in industrialized countries, and most cases of SCD in the young are related to inherited ion channel diseases. In this paper, we review a series of studies with murine transgenic models that revealed that some arrhythmias are associated with the CCS and may lead to SCD